Observations of iodine monoxide over three summers at the Indian Antarctic bases of Bharati and Maitri - Mahajan, A.; Biswas, M.; Beirle, S.; Wagner, T.; Schönhardt, A.; Benavent, N.; Saiz-Lopez, A. (Atmospheric Chemistry and Physics, 2021)
Iodine plays a vital role in oxidation chemistry over Antarctica, with past observations showing highly elevated levels of iodine oxide (IO) leading to severe depletion of boundary layer ozone in West Antarctica. Here, we present MAX-DOAS-based (multi-axis differential absorption spectroscopy) observations of IO over three summers (2015–2017) at the Indian Antarctic bases of Bharati and Maitri. IO was observed during all the campaigns with mixing ratios below 2 pptv (parts per trillion by volume) for the three summers, which are lower than the peak levels observed in West Antarctica. This suggests that sources in West Antarctica are different or stronger than sources of iodine compounds in East Antarctica, the nature of which is still uncertain. Vertical profiles estimated using a profile retrieval algorithm showed decreasing gradients with a peak in the lower boundary layer. The ground-based instrument retrieved vertical column densities (VCDs) were approximately a factor of 3 to 5 higher than the VCDs reported using satellite-based instruments, which is most likely related to the sensitivities of the measurement techniques. Air mass back-trajectory analysis failed to highlight a source region, with most of the air masses coming from coastal or continental regions. This study highlights the variation in iodine chemistry in different regions in Antarctica and the importance of a long-term dataset to validate models estimating the impacts of iodine chemistry.